The Religious Infrastructure of Al-Afgani and Abduh's Nationalism: Wasatiyyah as a Unified Reform Strategy in Colonial Egypt - Dian Malinda; Akhmad Fadhillah Kartono (Research Synergy Foundation, 2026)
Existing studies on Jamaluddin Al-Afgani and Muhammad Abduh have mostly stayed at the level of biography, examining their life histories and theological reform separately, rather than connecting their activism to the twin frameworks of nationalism and religious moderatism (wasatiyyah) as these unfolded together in colonial Egypt. This paper goes beyond biography by reading Al-Afgani and Abduh's joint contribution to nation-revival and religious moderation as a single, unified reform strategy, using a qualitative literature-study method that reads their biographical record against the conceptual lenses of anti-colonial nationalism and Qur'anic wasatiyyah. The study finds that the spirit of Al-Afgani's movement contributed to the revival of the community movement for independence and the development of science and literature in Egypt through three interlocking means: preparing the right environment by arousing religious values and nationalism, writing political articles in language that was beautiful yet easy to digest, and producing students who became prominent movers and writers in Egypt. Abduh himself was active in social and political movements, both through party participation and through writings that ignited the spirit of nationalism, while in the religious sphere he called for understanding Islamic law from its main sources while practicing moderation, anchored in his interpretation of the four guidances (hidayah) in surah al-Fatihah. The paper concludes that nationalism and moderatism are best understood not as two separate outcomes of two separate biographies but as two faces of one unified reform strategy.